Delayed Treatment of Traumatic Cervical Dislocation: A Case Report and Literature Review - Fabian Roland Bechet; Pierre Stassen; Dan Scorpie; Thierry Della Siega (Case Reports in Orthopedics)
Neglected unreduced cervical dislocation is very uncommon. In our case (a lady who stayed asymptomatic for 13 months before development of cervicobrachialgia), the anterior reduction/arthrodesis was easy, and we did not find any benefit from an additional posterior procedure thanks to a congenital block between C7 and T1 vertebral bodies. This point is nevertheless a matter of debate. After a review of the literature, we did not find any consensus about the ideal scheme and sequence to reduce and stabilize this delayed type of cervical trauma. We emphasize the need of dynamic radiographies to exclude unstable injuries but also a prereduction MRI (especially in unexaminable patients) to detect any dangerous disc fragment. If there is no visible change in the radiological status while attempting to reduce the dislocation by external maneuvers, there is little chance to reduce it successfully only by a single approach. Therefore, in irreducible delayed dislocations, it seems safer to prepare the reduction/fusion stage (either anterior/posterior, depending on the habits and skills of the surgeon) by a first stage carrying out a release of the fibrous tissues on the opposite side (either posterior to release the facet joints or anterior to release the intervertebral disc), followed by the reduction/fusion stage itself and then by a third stage to lock the level. Like many authors, we recommend an anterior approach first in case of an extruded disc visible on the MRI, and therefore, we show a preference for the anterior-posterior-anterior sequence in irreducible delayed cervical dislocations.